The Effect of Literacy-Habituation on Improving the Results of Assessment Competency Minimum Literacy Class-V SDN Binangun - Nafi'ah, Uun; Nurhidayati, Nurhidayati; Pangestika, Rintis Rizkia (Lectura : Jurnal Pendidikan, 2025)
Literacy is very important in all aspects of life, both in education, the workplace and in general society, and can be seen as a change that takes place slowly and gradually over a long period of time which is used as a basis for the development of Indonesian education. This research aims to determine the influence of literacy habits on the results of the Minimum Competency Assessment (AKM) literacy for class V students at SD Negeri Binangun in the 2023/2024 academic year with a research sample of 14 students. This research used a quantitative approach with a pre-experimental research design, namely One Group Pretest-Posttest Design. In data collection technique, data was collected by giving a pretest to measure students' initial literacy skills, followed by treatment in the form of literacy habits, and ending with a posttest to measure the increase in literacy skills. In analysis, the data was analyzed by measuring the level of significance between the pretest and posttest results to determine the influence of literacy habits on the AKM literacy results. The results of this research showed that literacy habits have a significant influence on the results of the Minimum Competency Assessment (AKM) for literacy of class V students, with a significance level (2-tailed) > 0.05, namely 0.179 > 0.05. In conclusion, literacy habits have a positive influence in improving the results of the Minimum Competency Assessment for literacy of class V students at SD Negeri Binangun.